We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
64
1
avatar

f(x)=-8+8x^3

f^-1(x)= ????

 Mar 3, 2019
 #1
avatar+101856 
+1

y = -8 + 8x^3

 

y + 8 = 8x^3

 

[ y + 8 ] / 8 = x^3       take the cube root

 

 ∛ [ y + 8 ] / 2 =  x         swap x and y

 

 ∛ [ x + 8 ] / 2 = y = the inverse

 

 

cool  cool cool

 Mar 4, 2019

4 Online Users